Influence of landscape moisture sources and topography on rock weathering patterns associated with wildfire. Issue 7 (27th February 2022) - Mol, Lisa; Grenfell, Michael
Abstract: From 9 March 2015, a wildfire burned an area of 25.7 km 2, or approximately half of the Jonkershoek catchment (Western Cape, South Africa), over the course of 3 days. During this period, large areas of fynbos and commercial forest plantations were razed, and rocks, including boulders and smaller rocks, were exposed to high temperatures. While a substantial body of work has been carried out to investigate the effects of wildfire on landscape development, less is known about the effect of wildfire on rock weathering within a landscape. Previous studies have reported the overall effect of wildfire on rock deterioration, but the effect of intra‐fire temperature differences associated with heat behaviour on a slope has not been sufficiently addressed. In this study we investigate the effects of topography and proximity to moisture on rock deterioration processes. In particular, we focus on the use of in‐field rock deterioration measurements and GIS to investigate the relative influences of distance from burn source, distance from moisture source and topographical positioning of the sample site. The results indicate that boulder size and lithology are of secondary importance to the placement of fire‐affected rocks within the wider topography of the landscape, and that rock exposure to moisture, also a function of landscape position, is likely to exacerbate the response of the rocks to heat. No direct correlation was observed between the type and severity of the outwardly visible damage sustained on the sampled rocks, and the size, lithology or proximity to burn source. We argue that these findings call for a re‐evaluation of fire‐related damage in the wider context of rock response as a function of topographical variations. Abstract : We present a new conceptual model that integrates topography and moisture availability into wildfire progression, and its effect on damage to rocks. Using rock weathering measurements and GIS analysis of the study site topography and watershed, we identified three distinct zones of damage, which show that evidence of fire intensity and soot deposition vary across a slope. We therefore propose that topography should be integrated into wildfire‐driven rock weathering studies, in light of enhanced wildfire occurrence associated with climate‐driven droughts.